Meningoencephalitis and optical neuritis caused by CRYPTOCOCCUS GATTII in an immunocompetent patient - Antunes de Souza, Beatriz; Carlos Silva Souza, Luiz; Oliveira Guilarde, Adriana; Augustus Costa Barbosa, Alexandre; Alves Ferreira Filho, Luiz; Antunes de Souza, Marta (Revista de Patologia Tropical / Journal of Tropical Pathology, 2020)
The following case is of a 59-year-old man, undergoing no medication, with no pathological history or others risk factors, who presented dizziness, fever and asthenia twenty days before admission. The patient was admitted for investigation when the asthenia intensified, followed by seizures. On admission, blood count, biochemical tests and chest computed tomography were normal, a serological test for anti-HIV proved negative, while the magnetic resonance of the brain showed signs suggestive of meningoencephalitis. Cerebrospinal fluid (CSF) analysis suggested bacterial meningitis due to increased leukocytes with a predominance of polymorphonuclear cells, reduced glucose and increased proteins as well as positive Gram cocci in pairs by Gram and negative fungi by India ink test. Treatment with ceftriaxone was started. Since there was no significant improvement, CSF analysis was repeated on the seventh day of treatment. Intracranial pressure was measured by manometry (29 mmHg) and CSF analysis showed the presence of encapsulated yeasts similar to Cryptococcus neoformans by the India ink test. The treatment was modified to liposomal amphotericin B and flucytosine; the intracranial hypertension was controlled by repeated CSF punctures. After fourteen days of antifungal treatment, the patient presented visual turbidity and bilateral papillar edema, so corticosteroid therapy was prescribed. The evolution was favorable, with progressive resolution of symptoms, improvement of CSF parameters and visual acuity. The patient was discharged eight weeks after admission, with outpatient guidance. Corticosteroid therapy associated with antifungal therapy proved to be beneficial in this case, since following the introduction of corticosteroids there was progressive visual improvement. KEY WORDS: Neurocryptococcosis; Cryptococcus gattii; ocular involvement; optic neuritis